Analysis of the Acquired Disorders of Reading in Kannada - Prathibha Karanth (Journal of All India Institute of Speech and Hearing, 1970)
The paper describes contemporary research on  the analysis of acquired disorders of reading within  the model-building approach, along  with details of the  classificatory system arrived thereby and the  tools used therein. The potential that  research on  the  analysis  of acquired disorders  of reading  in bi and multilinguals, specially among those one of whose languages is English, is highlighted.  The paper concludes by providing parallel lists in Kannada to  the  Coltheart word lists which are now  being  increasingly   used in  the analysis  of acquired disorders  of reading  in  English.